FACTORS AFFECTING THE UTILIZATION OF SERVICES IN THE DENTAL CLINIC OF PUSKESMAS KUTA MALAKA BIG ACEH DISTRICT - Mufi Zarni (Journal Dental Health, 2022)
Dental and oral health services are one of the development health efforts provided by the Puskesmas to the community. The number of patient visits at the dental clinic of the Kuta Malaka Health Center since 2020 has decreased. This study aims to determine the factors that influence the utilization of services at the dental clinic of the Kuta Malaka Public Health Center, Aceh Besar District. This research is a survey research using a cross sectional approach, the research subjects are 100 respondents. The sampling technique was carried out by purposive sampling. The measuring tools used are questionnaires and structured interviews. Data analysis used correlation analysis (P<0.05). Based on the results of data analysis, the previous treatment experience factor and the reference group (p=0.000) had a significant effect on service utilization at the dental clinic at the Kuta Malaka Health Center. It is suggested to the Puskesmas in order to improve the quality of service and provide patient-oriented based services to the community.